Moderasi Leverage dan Profitability Terhadap Dampak Corporate Social Responsibility (CSR) pada Nilai Perusahaan - Prasetiyo, Yudhi (Owner : Riset dan Jurnal Akuntansi, 2024)
In the current era of intense business competition, disclosure of social responsibility or CSR is not only a complement to companies in reporting their business entities, but is a principle that must be one of the main focuses in business continuity, because it is not only focused on profits, companies must also maintain environmental sustainability and provide social implications in the development and welfare of society. This research aims to determine the effect of CSR on company value as well as the moderating impact of debt (leverage) and profitability (NPM) on CSR and company value. The samples in this research are companies in the Agriculture, Forestry & Fisheries sectors that are listed on the IDX in the 2020-2022 period. The company selection used a purposive sampling method. The analysis technique used by the moderation analyst uses Smart PLS. The results of the research show that CSR does not have a significant influence on company value and debt (leverage) and profitability (NPM) are unable to moderate the influence of CSR on company value